Pengaruh Strategi Pembelajaran Matematika Lah Bako Terhadap Hasil Belajar Siswa Sebagai Bentuk Kearifan Budaya Lokal Kota Jember - Fury Styo Siskawati (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2017)
The purpose of the research is to know any significant effect of using Lah Bako mathematic learning strategy on students learning outcome as local wisdom in Jember. The kind of the research is exsperimental with quantitative approach. The subjects of the research are V grade students’. The data collecting methods are documentation, test and interview. After testing of the using Lah Bako mathematic learning strategy, the results of student outcome is better. The value of chi squre is 30,000 and table of chi squre is 3,481, it means that chi squre is higher than table of chi squre. Based on the results, it can be inferred that Ha is accepted and Ho is rejected, and the conclusion is, there is a significant effect of using Lah Bako mathematic learning strategy on students learning outcome as local wisdom in Jember. The suggestion of the research is, teacher as the main key on learning process must be creative and inovative to compile the learning strategy, where the learning strategy is used not only for reaching the learning purpose but also learning strategy which invite the students for knowing surrounding local wisdom, as using Lah Bako (Latihan Hitung Bangun Kongkret) learning strategy that it’s name of traditional dance from Jember.Keywords: Lah Bako strategy, learning outcome.